Comparisons of the v11.1 Orbiting Carbon Observatory‐2 (OCO‐2) XCO2 Measurements With GGG2020 TCCON - Saswati Das; Matthäus Kiel; Joshua Laughner; Gregory Osterman; Christopher W. O’Dell; Thomas E. Taylor; Brendan Fisher; Frédéric Chevallier; Nicholas M. Deutscher; Manvendra K. Dubey; Dietrich G. Feist; Omaira Garcia; et al. (Earth and Space Science, 2025)
Abstract The Orbiting Carbon Observatory 2 (OCO‐2) is NASA's first Earth observation satellite mission dedicated to studying the sources and sinks of carbon dioxide (CO2) on a global scale. The observations of reflected sunlight are inverted in a retrieval algorithm to produce estimates of the dry air mole‐fractions of CO2 (XCO2). The OCO‐2 Level 2 data release, version 11.1 (v11.1) retrievals from the Atmospheric Carbon Observations from Space (ACOS) algorithm, includes significant improvements in the XCO2 data product compared to older OCO‐2 data versions. This work compares the v11.1 XCO2 from OCO‐2 against XCO2 estimates collected from a global ground‐based network known as the Total Carbon Column Observing Network (TCCON), OCO‐2's primary validation source. The OCO‐2 project provides a version of the Level 2 data product, called “lite” files that include calibrated and bias‐corrected XCO2 values, accessible together with all OCO‐2 data products through the NASA Goddard Earth Sciences Data and Information Services Center (GES DISC). This work shows that OCO‐2 XCO2 observations made between September 2014 and December 2023, after quality filtering and the application of an averaging kernel correction, agree well with coincident TCCON data for all OCO‐2 observational modes of land (nadir, glint, target) and ocean (glint). The aggregated, bias‐corrected, and quality‐filtered absolute average bias values are less than or equal to 0.20 parts per million (ppm) globally for all OCO‐2 observation modes, where the biases do not indicate a statistically significant time dependence. The land nadir/glint mode has the lowest bias value of −0.03 ± 0.85 ppm.